Learning hijaiyah letters through sign language using marbel application for students with hearing impairment - Mega Iswari; Nurhastuti Nurhastuti; Retno Triswandari; Zulmiyetri Zulmiyetri; Johandri Taufan; Ringgi Rahmat Fitra; Gaby Arnez; Setia Budi (Indonesian Counselor Association (IKI), 2024)
The advancements of knowledge and technology in the fourth industrial revolution have influenced learning settings at school. Teachers have to develop new learning methods, models, and media to help improve their students' learning outcomes. The technology that is becoming popular among students is Android-based media. Students at school are diverse and so are students at special education schools(SLB). Students with hearing impairment are those who suffer from hard of hearing and hearing loss. Teachers must get their students to make the most of their residual hearing and other senses like touch and sight when learning, especially during difficult subjects. One of the subjects that the students consider the hardest is religious education because it has a lot of practice and memorization. Hijaiyah is 30 letters of the Arabic alphabet and learning them becomes the core competency in reading the Quran. Teachers can use sign language as their teaching strategy. Sign language is a non-verbal language used by hearing-impaired people. However, sign language is still not commonly used among teachers at special education schools. This research used Research and Development model. The data were collected through observations, interviews, documentation, and literature study. The data analysis was conducted using data reduction, data presentation, and data interpretation. The product of the research is an Android application for learning hijaiyah letters through sign language for students with hearing impairment.